Production and characterisation of a biosurfactant based on Acinetobacter sp. V2 and its potential use for environmental applications. Issue 6 (2nd November 2022) - Ntshingila, Nokwanda Prudence; Jimoh, Abdullahi Adekilekun; Lin, Johnson
ABSTRACT: Maximum biosurfactant production was achieved in an optimised process containing pH 8 and 30°C, with waste coconut oil and ammonium sulphate at carbon-to-nitrogen ratio of 1:7. The structural composition of Acinetobacter sp. V2 biosurfactant was polymeric, consisting of a protein complex and a fatty acid. This biosurfactant exhibited stability to different pH and temperature conditions. The emulsifying property was affected by changes in NaCl concentration. The V2 biosurfactant was effective in removing heavy metals present in acid mine drainage effluents and contaminated vegetables.